The Tromsø Recommendations for Citation of Research Data in Linguistics: Collaboration illustrated - Andreassen, Helene N. (Ravnetrykk, 2020)
The Tromsø Recommendations for Citation of Research Data in Linguistics were published in 2019, with a twofold objective: To provide a guide on how to cite research data in linguistics according to good practices, and to contribute to making linguistics a more transparent science. This paper presents the rationale behind the recommendations as well as the development process. The goal is to demonstrate how collaboration, engagement, and different types of expertise are crucial factors to progress towards a culture of sharing of knowledge.